The role of school library in academic motivation of secondary school students in Osun State, Nigeria (2017)
The aim of this study is to evaluate the use of school library materials and Services available in promoting students’ academic motivation in selected Secondary Schools in Osun State, Nigeria. The study adopts multistage random sampling technique to choose the sample size from one senatorial district out of the three senatorial districts in Osun State. 240 students were randomly selected from the six secondary schools selected for the purpose of this study. A self-administered questionnaire was employed as the instrument for data collection. The questionnaires were distributed in the classrooms to those who agreed to participate in the study. There were 241 respondents; 120 males (49.8%) and 121 females (50.2%). Their ages ranged from 11 to 20 years. Majority of the respondents (53.5%) use the library weekly; 36.5% daily and 10.4% use the library monthly. The students that used the library daily were predominantly boys (49.2%) and most of those who used the library weekly were females (71.1%). On the main reason for using the school library; to study individually has the highest Variable Score (VS) of 3.61. The importance of some available library Services to the students shows that “finding a place to do private study” has the highest VS of 2.6 while “finding electrical outlets in seating areas” has the lowest variable score of 1.49. The frequency of use of some available library resources shows that using the library textbooks has the highest VS of 2.92 while the use of CD-ROM has the lowest variable score of 1.54. “Finding relevant materials for better understanding of subjects”, “reading and taking notes” have the highest VS of 2.88 while 2.85 respectively regarding what they enjoy in the library. “I can always go online and also check my email” has the lowest variable score of 2.32 among the factors that motivate the students in the library. The students used the school libraries on a slightly lower frequency daily. One of the reasons for visiting the library was significantly not to browse the internet despite the fact that this is important to them and the least factor that motivates them is their experience in online activities in the library. It is generally clear that a lot of funding still need to go into acquiring new technologies for use in Nigerian School libraries.